2019
DOI: 10.7759/cureus.4458
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sofosbuvir and Ribavirin for Treating Chronic Hepatitis C, Genotype 3: Experience of a Tertiary Care Hospital at Karachi, Pakistan

Abstract: Background It is estimated that approximately 10 million individuals in Pakistan are infected with hepatitis C virus (HCV). Historically, it was very difficult not just to cure but even treat HCV as available options did not have desirable outcomes. However, the approval of directly acting antiviral (DAA) drugs has revolutionized treatment and management. These are specific proteases and polymerase inhibitors with profound capability for accomplishing elimination and overtime eradication of the viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Mainly there are adults' studies and in paediatrics Hashmi MA et al reported mean age of 10years and Alvi MA et al reported 14± 2.5years. 12,17,18 Male to female ratio in our study was 1.3, male were predominant same as reported by Hashmi et al 1.7 times male and Alvi MA et al 1.6 times male, even higher ratio of males in their studies as compared to our study. 12,17 Nine patients in our study were less than 6 years of age and youngest one was 3 years old.…”
Section: Discussionsupporting
confidence: 87%
“…Mainly there are adults' studies and in paediatrics Hashmi MA et al reported mean age of 10years and Alvi MA et al reported 14± 2.5years. 12,17,18 Male to female ratio in our study was 1.3, male were predominant same as reported by Hashmi et al 1.7 times male and Alvi MA et al 1.6 times male, even higher ratio of males in their studies as compared to our study. 12,17 Nine patients in our study were less than 6 years of age and youngest one was 3 years old.…”
Section: Discussionsupporting
confidence: 87%
“…Hepatitis C Virus (HCV) which is a leading cause of chronic liver disease (CLD) and decompensated liver disease (DCLD) affects about 170-200 million individuals worldwide [ 1 ]. In Pakistan, approximately 10 million individuals are infected with HCV and this burden is expected to grow in the coming years [ 2 ]. Several efforts are being done by the officials in Pakistan to control the spread of disease as well as to timely manage all those suffering from it.…”
Section: Introductionmentioning
confidence: 99%
“…SOF plus RIB therapy has been depicted to be safest antiviral therapy in local as well as international studies in the recent years. 1,4,12,13,14 All the side effects with this regimen are manageable and possess low threat as compared to previously available treatments. 25…”
Section: Resultsmentioning
confidence: 99%
“…More than 200 million people are estimated to be affected by hepatitis C virus (HCV) around the globe and it is considered to be the leading cause of chronic liver disease and decompensated liver disease especially in developing countries. 1,2 Amongst various genotypes globally, genotype 1 has an overall share of 46% while genotype 3 accounts for nearly 22% of the cases. In Pakistan, the burden of HCV seems to involve more than 10 million individuals and the numbers are growing every day.…”
Section: Introductionmentioning
confidence: 99%